The Role of Immediate Early Genes in Neuropsychiatric Illness - Gallitano, Amelia L. (Frontiers Media SA, 2020)
The search to identify the genes for mental illnesses has been complicated by the critical, yet poorly understood, role that environment plays in development of these disorders. Immediate early genes link environmental events, such as stress, to long-term changes in the brain. These genes play critical roles in numerous processes that are affected in mental illnesses including synaptic plasticity and memory, growth factor regulation, myelination and vascularization, and immune function. Thus, dysfunction in the activation of immediate early genes may explain the dual genetic and environmental etiology of these enigmatic illnesses. The current Research Topic explores the role of immediate early genes in processes that may underlie the symptoms, or risk to develop, neuropsychiatric illnesses.